Impact of Spirulina Chikki Supplementation on Nutritional Status of Children: An Intervention Study in Tumkur District of Karnataka, India - Kashyap, Gyan Chandra; Sarala, R.; Manjunath, Usha (Frontiers in Pediatrics, 2022)
Objective: To assess the impact of Spirulina Chikki supplementation on the nutritional status of children (6 months-6 years). Design: A cross-sectional study design was adopted to assess the changes in nutritional status among the children (after 12 months of intervention period). The bassline and endline assessment were carried out from September 2020 to August 2021 respectively. Setting: Total 106 villages (108 Anganwadi Centres in 9 circles) from Tumkur District were covered. Methods: Children aged 6 months-6 years were the study subjects. Anthropometric measurements viz., height, weight, and mid-arm circumference were collected from total 971 and 838 children during baseline and endline assessments correspondingly. The information on children's health and nutrition status was gathered from the mothers of sampled children. WHO’s Anthro and AnthroPlus software were utilized to estimate the anthropometric measurements (Stunting, wasting and underweight) of study participants. Results: The study found apparent disparities in the prevalence of stunting, wasting and underweight among the male and female children. There was a significant decline viz., 4% (28.6%- baseline to 24.5%- end line) in the prevalence of severe wasting. Also, severe stunting dropped by 6% at end line (30%-end-line to 24%- baseline). Improvement in nutritional status was evident among both female male children in all three indicators stunting, wasting, and underweight. Mid-upper arm circumference (MUAC) measurement shows substantial improvements from baseline to end line: SAM (5.3% to 0.6%), MAM (23% to 9%) and normal (72% to 91%). The study discloses significant improvements in the nutritional status among those children who consumed spirulina chikkis/granules for a longer duration viz., 9-10 months as compared to those who consumed for lesser duration. Conclusions: Findings reveal improvement in nutritional status among the beneficiaries who consumed spirulina chikki/granules as per the recommended quantity (amount) during the intervention period. Post intervention, spirulina chikki supplementation for nutritional intervention is implied to address large scale malnutrition among young children.